Exploring the Students' Reading, Writing, and Numeracy Skills in Southeast Maluku Regency Coastal Elementary Schools - Anasufi Banawi; Adam Latuconsina; Satiah Latuconsina (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to explore students' reading, writing, and numeracy skills in ten coastal elementary schools targeted for the 2021 Elementary School Quality Improvement Program. This study used an ex-post-facto quantitative descriptive method. Â The data source is a database of the 2021 Elementary School Face-to-Face Learning Quality Improvement Program in Southeast Maluku Regency, i.e., the literacy and numeracy skills scores of 500 students. Normalized gain was used to determine the magnitude of the increase in scores from the pre-test and post-test. The results showed that eight elementary schools (80%) had a mean literacy final score of more than 60 (mean 68.23). The final score of literacy in each class is above 60, with the highest average final score achieved by Grade 3 (74.83). The increase in students' reading and writing literacy scores was still in the Low category (0.28). Two elementary schools (20%) have an average final numeracy score below 60. In general, the average final numeracy score is above 60 (63.40). The lowest numeracy score is in Grade 4 (58.31). The increase in numeracy skill scores is still in the low category (0.23). The results indicate the school's need for reflection, evaluation, follow-up plans, and program sustainability to strengthen students' skills.Keywords: reading and writing literacy, numeracy literacy, elementary school students.Â AbstrakPenelitian ini bertujuan untuk mengeksplorasi kemampuan literasi baca tulis dan numerasi peserta didik di sepuluh Sekolah Dasar (SD) daerah pesisir yang menjadi sasaran Program Kejar Mutu Sekolah Dasar Tahun 2021. Metode deskriptif kuantitatif ex-post-facto digunakan dalam penelitian ini. Sumber data berupa database Program Kejar Mutu Pembelajaran Tatap Muka Sekolah Dasar Tahun 2021 di Kabupaten Maluku Tenggara, yakni skor kemampuan literasi baca tulis dan numerasi dari 500 peserta didik. Gain-ternormalisasi digunakan untuk mengetahui besarnya peningkatan skor dari pre-test dan post-test. Hasil penelitian menunjukkan delapan SD (80%) telah mempunyai rerata skor akhir literasi baca tulis lebih dari 60 (rerata 68,23). Skor akhir literasi baca tulis tiap kelas di atas 60, rerata skor akhir tertinggi dicapai Kelas-3 (74,83). Peningkatan skor kemampuan literasi baca tulis peserta didik masih dalam kategori Rendah (0,28). Terdapat dua SD (20%) yang memiliki rerata skor akhir numerasi di bawah 60. Secara umum rerata skor akhir numerasi berada di atas 60 (63,40). Skor numerasi terendah pada Kelas-4 (58,31). Peningkatan skor kemampuan numerasi masih dalam kategori Rendah (0,23). Hasil yang ada mengindikasikan perlunya refleksi, evaluasi dan rencana tindak lanjut serta keberlanjutan program oleh pihak sekolah untuk memperkuat kemampuan peserta didik.Kata kunci: literasi membaca dan menulis, literasi numerasi, siswa sekolah dasar.